Comparison of Depression Levels between Medical and Engineering Students at Universitas Muhammadiyah Jakarta - Nadila, Riska Indri; Renovaldi, Dede (Muhammadiyah Medical Journal, 2025)
Background: Medicine and engineering faculties are noted for their vigorous learning intensity and high degree of academic difficulty, making them vulnerable to mental health illnesses such as depression. Purpose: To compare depression levels between medical and engineering students at Universitas Muhammadiyah Jakarta. Method: This study employed a cross-sectional design. Medical and Engineering students were given the Beck Depression Inventory II (BDI-II) questionnaire. The sample size consists of 152 people, collected through purposive sampling. The Mann-Whitney test was used for analysis (p = 0.05, 95% CI). Result: Age 21 (25.0%) was the most frequent age, while age 17 (2.6%) was the least frequent. Based on gender, the male respondents consisted of 87 people (57.2%), and the female respondents consisted of 65 (42.8%). The medical and engineering student groups each had 76 respondents (50.0%). Only 40.8% of medical students reported depression, compared to 63.1% of engineering students (p = 0.001). Conclusion: Engineering students experience more depression than medical students.